Measuring the Magnitude of Film Tourism as a Catalyst of the Indonesian Tourism Sector: A Case Study of Laskar Pelangi Film in Belitung Island - Budhi Fatanza Wiratama; Ernawati Pasaribu (Pusbindiklatren Bappenas, 2022)
The creative economy is a new paradigm to be reckoned with. Unfortunately, film as the priority sub-sector of Indonesia's Creative Economy failed to become one of the five sub-sectors with the largest multiplier effect to other sub-sectors of the creative economy. There is an immeasurable impact of film on the tourism sector which is known as film tourism. This research conducts empirical evidence on the case study of Belitung Island and the Laskar Pelangi film to measure the magnitude of the film tourism effect. The analytical method used in this study is the ARIMA (Autoregressive Integrated Moving Average) intervention modelling. The results of the intervention model show that the Laskar Pelangi film and the Kata Museum of Andrea Hirata have a significant direct effect on the tourist arrival in Belitung Island. Meanwhile, the influence of the Tanjung Kelayang Tourism SEZ was significant almost one year after it was established. The increase in tourist arrival due to Laskar Pelangi film tourism is two times higher than without the effect, indicating that the film tourism phenomenon is possible to become a new form of innovation that is effective as a catalyst for the future of Indonesia's tourism sector.